THE INFLUENCE OF ARAB GEOGRAPHICAL RESEARCH ON PUPILS' GEOGRAPHICAL CULTURE FORMATION - O. Amangeldi; T. Kurt; L. Tokayeva; A. Nurbayeva (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы)
This article examines the influence of Arab geographical studies on the formation of pupils' geographical culture. The analysis of school textbooks has shown that the achievements of Arab explorers and geographers are not sufficiently covered, leading to a one-sided perception of the history of geographical science. The study examined the achievements of Arab scientists, their contribution to world science, and possible ways of integrating this knowledge into the educational process.